Establishment of Reference Intervals for Blood Urea Levels in Young Prospective Medical Students Undergoing Health Checkup at BPKIHS, Dharan, Nepal (Health Renaissance, 2011)
Background: Reference values or reference intervals are set of values of a certain type of quantity obtainable from a single individual or a group of individuals corresponding specific description.Objective: This study highlights the approach for determining the reference intervals for blood urea in a healthy population and establishes its upper and lower reference limits.Subjects and methods: A descriptive study was carried out in the Department of Biochemistry B. P. Koirala Institute of Health Sciences from June 2009 to August 2009. International federation of Clinical Chemistry and Laboratory Medicine (IFCC) priori sampling technique was used. Blood urea was estimated by diacetyl monoxime (DAM) and Glutamate Dehydrogenase (GLDH) kinetic methods. Reference intervals were defined as mean ± 1.96 SD. Mean and standard deviation for blood urea values were expressed as descriptive statistics.Results: The study included 60 individuals (36) 63% males and (24) 37 % females. Blood urea values by GLDH kinetic and DAM methods were 22.07 ± 5.6 mg/dl and 27.1 ±8.79 mg/dl respectively. Reference values of blood urea by GLDH kinetic and DAM methods were 16-28 mg/dl and 18-36 mg/dl respectively.Conclusions: This study highlights the establishment of reference intervals of blood urea levels from a healthy population. The reference intervals would enable the laboratory personnel and the clinicians to interpret the medical data.Health Renaissance, May-Aug 2010; Vol 8 (No.2):126-129